Implementasi Pendidikan Karakter di Pesantren Berbasis Multikultural - Miftahul Arifin; Imam Wahyono; Vina Rohmatul Ummah; Fathi Hidayah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to explore the implementation of multicultural-based character education at Ibnu Sina Islamic Boarding School. In the contemporary Islamic education landscape, Islamic boarding schools face sociological challenges in the form of diverse student backgrounds that have the potential to trigger horizontal conflict. Using a qualitative case study approach, this study reveals how the core values ​​of Ahlussunnah wal Jama'ah (Aswaja), Tawassuth, Tasamuh, and ’Adalah are integrated with Thomas Lickona's character education theory. The findings indicate that Islamic boarding schools deliberately construct a hidden character curriculum through a policy of dormitory heterogeneity and the exemplary behavior of caregivers. However, its effectiveness is still influenced by determinant factors such as the lack of intensive mentoring for new students. This study concludes that Islamic boarding schools function as miniature multicultural societies capable of transforming potential conflicts into instruments for strengthening inclusive character.